PRAKTIK PEMBACAAN YASIN FADILAH DI MASYARAKAT PERSPEKTIF LIVING QUR’AN DAN ANALISIS PERUBAHAN SOSIAL (Studi Kasus di Majelis Taklim Al-Muthmainnah Desa Lemahabang Kulon, Kec. Lemahabang, Kab. Cirebon) - Luthfiatus Shobahah (UIN Siber Syekh Nurjati Cirebon, 2017)
This article focus on investigation about practice of reciting Alquran perspective of living Quran and analysing social civilization. Living Quran is new approach for understanding sense of Quran with contextual concept. Practice of reciting Alquran which did by society is one of way to understand sense of Alquran. Research of living Quran be important because understanding and interpreting Alquran not only on library study facing texts of Alquran. Nevertheless, reception of society to practice of reciting Alquran is process an assembling and interpreting Alquran by context. Reception of Alquran theory and social civilization suitable for analysing of living Quran to find out social phenomenon related with presence of Alquran in certain community.